Effects of pollution on freshwater animal communities (Zoological Records and Reviews, 2024)
Freshwater ecosystems are among the most pollution-impacted habitats on Earth, yet multi-stressor assessments thatsimultaneously characterise the effects of nutrient enrichment, organic loading, micropollutants, and heavy metals onanimal community structure remain rare across the Scandinavian and Northern European context. This study quantifiesthe individual and combined effects of four pollution categories on macroinvertebrate, fish, and amphibian communitiesacross 36 freshwater sites spanning a pollution gradient in Sweden, Finland, and Denmark (n = 12,418 individualrecords, 2021-2023). Nutrient enrichment (total phosphorus > 0.10 mg/L) was the most prevalent stressor (present at72.2% of sites), significantly reducing EPT (Ephemeroptera, Plecoptera, Trichoptera) richness by 48.3 +- 6.1% relative toreference sites (GLMM: z = 6.84, p < 0.001). Organic pollution (BOD5 > 4 mg/L) reduced fish species richness by 34.7 +-5.8% and shifted assemblages towards pollution-tolerant cyprinids. Micropollutant mixtures (pharmaceutical compounds,pesticide residues) at peri-urban sites were associated with intersex prevalence of 31.4 +- 7.2% in roach (Rutilus rutilus),consistent with endocrine disruption by estrogenic compounds. Heavy metal gradients (Cu, Zn, Pb) in mine-affectedstreams correlated negatively with macroinvertebrate ASPT scores (r = -0.81, p < 0.001). Multi-stressor interactionanalysis revealed predominantly additive effects of nutrient and organic stressors on EPT richness, but synergistic effectsof micropollutants combined with nutrient enrichment on fish endocrine endpoints. These findings providestressor-specific management targets for achieving EU Water Framework Directive good ecological status inScandinavian and Northern European rivers.